Exfoliation of Active Materials Synchronized with Electrolyte Extraction from Spent Lithium‐Ion Batteries by Supercritical CO2. Issue 20 (20th May 2022) - Mu, Deying; Liang, Jianquan; Zhang, Jian; Wang, Yue; Jin, Shan; Dai, Changsong
Abstract: Safe and harmless treatment of electrolyte is a critical environment issue for spent lithium‐ion battery recycling; the effective separation of cathode materials from aluminum foil is a key technology for resource utilization. Previous studies have never considered the two as a whole. This study introduced supercritical CO2 technology to realize the integrated treatment of electrolyte removal and cathode material exfoliation. The results indicated that the optimum parameter was obtained at a temperature of 38 °C, a time of 15 min and a pressure of 10 MPa. The peeling efficiency of cathode material from Al foil reached 98.86 wt.%. Mechanism analysis confirmed that the separation of Al foil and cathode material was the result of the weakened adhesion of electrode interface, which can be attributed to the removal of the organic component including carbonate‐based organic solution and organic binder caused by the fluid extraction process. Abstract : Supercritical CO2 extraction technology was innovatively utilized to extract electrolyte and simultaneously liberate cathode materials from spent lithium ion batteries, which simplified separation procedure, achieved high peeling‐off efficiency and improved product purity. The mechanism of supercritical CO2 extraction and interface separation were also explored.